Assessment of ADP-induced platelet aggregation with light transmission aggregometry and multiple electrode platelet aggregometry before and after clopidogrel treatment - Sibbing, Dirk; Braun, Siegmund; Jawansky, Stefan; Vogt, Wolfgang; Mehilli, Julinda; Schömig, Albert; Kastrati, Adnan; von Beckerath, Nicolas (Thrombosis and haemostasis, 2008)
The level of platelet aggregation, measured with light transmission aggregometry (LTA) in platelet rich plasma (PRP), has been shown to predict outcomes after percutaneous coronary intervention (PCI). However, measuring parameters of platelet function with LTA is time consuming and weakly standardized. Thus, a fast and standardized method to assess platelet function after clopidogrel treatment would be of great value for clinical practice. A new method, multiple electrode platelet aggregometry (MEA), to rapidly measure platelet aggregation in whole blood has recently been developed. The aim of this study was to assess parameters of platelet function with MEA and LTA before and after administration of 600 mg clopidogrel. Blood samples from 149 patients scheduled for coronary angiography were taken after clopidogrel treatment; in addition, in 60 of the patients samples were available before clopidogrel treatment. ADP-induced platelet aggregation was measured with LTA and simultaneously in whole blood with MEA on the Multiplate analyzer. Platelet aggregation measured with MEA decreased significantly after clopidogrel treatment (P < 0.0001). ADP-induced platelet aggregation assessed with MEA and LTA correlated significantly (Spearman rank correlation coefficient = 0.71; P < 0.0001). The results of MEA, a fast and standardized method to assess the platelet response to ADP prior to and after clopidogrel treatment, correlate well with LTA.